Tourism Socialization: Training in Guiding Educational Songket Weaving Tours - Fernando Fasandra; Khairunnisa Khairunnisa; Naufal Hibatullah; Fadlul Rahman; Nitasri Murawaty Girsang; Septriani Septriani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Community service activities are one of the main responsibilities of lecturers as educators in the university environment. This community service aims to provide knowledge and improve the ability to guide educational tourism related to woven songket to enhance the promotion of SMEs through tourism. The community service activities are conducted at the SME